No straight lines – young women’s perceptions of their mental health and wellbeing during and after pregnancy: a systematic review and meta-ethnography - Grace Lucas (BMC Women's Health, 2019)
Abstract Background Young mothers face mental health challenges during and after pregnancy including increased rates of depression compared to older mothers. While the prevention of teenage pregnancy in countries such as the United States and the United Kingdom has been a focus for policy and research in recent decades, the need to understand young women’s own experiences has been highlighted. The aim of this meta-ethnography was to examine young women’s perceptions of their mental health and wellbeing during and after pregnancy to provide new understandings of those experiences. Methods A systematic review and meta-ethnographic synthesis of qualitative research was conducted. Seven databases were systematically searched and forward and backward searching conducted. Papers were included if they were from Organisation for Economic Co-operation and Development countries and explored mental health and wellbeing experiences of young mothers (age under 20 in pregnancy; under 25 at time of research) as a primary research question – or where evidence about mental health and wellbeing from participants was foregrounded. Nineteen papers were identified and the Critical Appraisal Skills Programme checklist for qualitative research used to appraise the evidence. Following the seven-step process of meta-ethnography, key constructs were examined within each study and then translated into one another. Results Seven translated themes were identified forming a new line of argument wherein mental health and wellbeing was analysed as relating to individual bodily experiences; tied into past and present relationships; underpinned by economic insecurity and entangled with feelings of societal surveillance. There were ‘no straight lines’ in young women’s experiences, which were more complex than dominant narratives around overcoming adversity suggest. Conclusions The synthesis concludes that health and social care professionals need to reflect on the operation of power and stigma in young women’s lives and its impact on wellbeing. It adds to understanding of young women’s mental health and wellbeing during and after pregnancy as located in physical and structural factors rather than individual capacities alone.